2019
DOI: 10.1186/s40643-019-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimized sampling protocol for mass spectrometry-based metabolomics in Streptomyces

Abstract: In quantitative metabolomics studies, the most crucial step was arresting snapshots of all interesting metabolites. However, the procedure customized for Streptomyces was so rare that most studies consulted the procedure from other bacteria even yeast, leading to inaccurate and unreliable metabolomics analysis. In this study, a base solution (acetone: ethanol = 1:1, mol/mol) was added to a quenching solution to keep the integrity of the cell membrane. Based on the molar transition energy (ET) of the organic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…An optimized method might not be suitable for a similar bacteria strain implying the different aims and setup of the experiment [ 65 ]. Liu et al [ 66 ] highlighted the importance of clear sample preparation method designated for bacterial metabolomics in obtaining high-accuracy and high-reliability data analysis. Most metabolomic studies reported adopting the available or existing procedures conducted for other bacteria or yeast, resulting in inaccurate analysis and conclusion [ 66 ].…”
Section: Sample Preparation Methods For Bacterial Metabolitesmentioning
confidence: 99%
See 4 more Smart Citations
“…An optimized method might not be suitable for a similar bacteria strain implying the different aims and setup of the experiment [ 65 ]. Liu et al [ 66 ] highlighted the importance of clear sample preparation method designated for bacterial metabolomics in obtaining high-accuracy and high-reliability data analysis. Most metabolomic studies reported adopting the available or existing procedures conducted for other bacteria or yeast, resulting in inaccurate analysis and conclusion [ 66 ].…”
Section: Sample Preparation Methods For Bacterial Metabolitesmentioning
confidence: 99%
“…Liu et al [ 66 ] highlighted the importance of clear sample preparation method designated for bacterial metabolomics in obtaining high-accuracy and high-reliability data analysis. Most metabolomic studies reported adopting the available or existing procedures conducted for other bacteria or yeast, resulting in inaccurate analysis and conclusion [ 66 ]. A number of optimization studies on metabolite sample preparation methods have been reported on various species of bacteria [ 30 , 53 , 59 ].…”
Section: Sample Preparation Methods For Bacterial Metabolitesmentioning
confidence: 99%
See 3 more Smart Citations